JARINGAN SOSIAL DAN MORAL EKONOMI PEDAGANG PEKANAN - ANGGRE WIRAWAN (Perspektif Sosiologi, 2012)
Abstract: Limitations of existing public access in the farm to the city because  long distances result in delays their business to satisfy necessities of life. It is the basic for the merchants, especially the Minang ethnic see it as a business opportunity. Distance and location is not easy because of poor road infrastructure, perforated, rocky, dusty, muddy even if rain do not hamper  them to selling in plantation weeks. In trading activity, existing barriers can be faced by Minang ethnic merchants to strengthen the network and the presence of other forms of moral economy that is built on the traders. Such in situation also seen in minangnese who selling in the area around the Kota Pinang plantations, south labuhanbatu build the social networks and promoting values ​​of moral economy in trading activities. Keywords: Trading activity, strengthen the network,  and moral economy.